Constructing a family tree in an online space as an act of digital curation: an auto-hermeneutics study - Porter, Donovan Stuart (Department of Knowledge and Information Stewardship, 2026)
Digital curation requires taking appropriate actions throughout the lifecycle of digital data. Digital curation of research data in a lifecycle is referred to as the custodial approach, while the pragmatic approach is the curation of digital content in everyday life, such as on websites or social media platforms (Dallas, 2016). Online genealogy, in which a genealogist is using a digital platform to construct a family tree and search for source documents, is an example of the pragmatic approach to digital curation. In this study I investigate genealogy through the lens of digital curation to discover how users curate their genealogical information on a major genealogy website, Ancestry.com. In this way, I consider how online genealogy can be studied as an example of the pragmatic approach to digital curation. This is a qualitative study making use of auto-hermeneutics – I collected data by systematic self-observation (SSO) and analysed it by interpretative phenomenological analysis (IPA). I reconstructed my own family tree in Ancestry.com, evaluating the research hints offered to me by the website algorithm and the member-constructed family trees which contained my ancestors. I found, among other things, that Ancestry.com makes the tree construction process easy and the research hints provided by the website can be verified if caution is exercised, but the same cannot be said for the family trees constructed by Ancestry.com members, many of whom do not practise caution in this endeavour. Study recommendations include a change in the data fields Ancestry.com uses for data capture from members or a change in which it processes and displays that data to ensure that omission of data does not cause incongruous errors to be displayed; and better visibility of the website's guidance on good research techniques to avoid the perpetuation of research errors. Ancestry.com already has verification functionalities which, if applied more widely, have the potential to improve the curation of member-constructed trees.